Management Practices and the Partial Government Ownership of Firms in the Middle East and North Africa Region - Islam, Asif M.; Gatti, Roberta (World Bank, Washington, DC, 2022)
A wealth of evidence has shown the positive effects of better management practices on firms. More recent evidence has highlighted that ownership matters for several developing and advanced economies. However, this relationship has not been studied extensively for economies in the Middle East and North Africa, a region where the presence of the government in the productive sphere looms large. This study contributes to this gap in the literature by exploring how partial government ownership can influence the management practices of medium and large formal firms in the Middle East and North Africa. Using two waves of Enterprise Surveys undertaken in 2013 and 2019/2020, the evidence points at a negative relationship between partial government ownership and management practices in the developing Middle East and North Africa region. A subsample of panel firms confirms these findings. Analysis conducted for firms surveyed in Europe and Central Asia in the same time frame does not show a similar negative relationship between partial government ownership and management practices, highlighting regional heterogeneity.